Evidence Synthesis Instructional Offerings in Library and Information Science Programs - Lafferty, Meghan; Premji, Zahra; Herold, Philip; Kocher, Megan; Marsalis, Scott (Evidence Based Library and Information Practice, 2024)
Objective – The goal of this study was to determine the extent to which evidence synthesis (ES) is incorporated into American Library Association (ALA)-accredited master’s level Library and Information Studies (LIS) programs. The study considered the depth of coverage, interest in additional curriculum content, and preferences for expanding existing coverage.Methods – A cross-sectional survey was implemented. Program administrators and instructors currently involved with ALA-accredited master’s level LIS programs in Canada and the United States were eligible to participate. Recruitment emails targeted faculty and administrators from a directory of institutions offering ALA-accredited MLIS programs.Results – 26 eligible responses from 20 unique institutions were obtained. Most respondents reported that ES is incorporated into the curriculum, albeit only briefly in most cases. Most of the respondents expressed interest in incorporating more ES content into the curriculum, specifically as a portion of a course. A greater number of respondents would prefer to bring in external guest speakers to teach the ES content, but a small percentage were interested in training for existing LIS instructors.Conclusion – In-depth instruction on ES in LIS programs is currently limited. However, there appears to be interest in increasing ES content in curricula, primarily in the form of guest lecturers.